1999
DOI: 10.1111/j.1600-051x.1999.tb02524.x
|View full text |Cite
|
Sign up to set email alerts
|

Unusual peripheral odontogenic tumors in the differential diagnosis of gingival swellings

Abstract: Abstract. Differential diagnosis of gingival mass lesions includes several conditions and causes. Peripheral odontogenic tumors may mimic gingival swellings and, although rare, must be included in the differential diagnosis. The purpose of this article is to describe 3 different cases of peripheral odontogenic tumors and to discuss the differential diagnosis of gingival swelling. Histologic examination is mandatory when localized gingival swellings are surgically removed. Zusammenfassung Ungewöhnliche periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 23 publications
0
23
0
1
Order By: Relevance
“…Clinical differential diagnosis of OFM cases reported has varied in the literature and includes fibrous hyperplasia, giant cell fibroma, peripheral giant cell granuloma, peripheral ossifying fibroma, peripheral odontogenic fibroma, squamous papilloma, mucoceole and pyogenic granuloma. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] To the authors knowledge, this is the first case reported where OFM has resembled the appearance of DG.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Clinical differential diagnosis of OFM cases reported has varied in the literature and includes fibrous hyperplasia, giant cell fibroma, peripheral giant cell granuloma, peripheral ossifying fibroma, peripheral odontogenic fibroma, squamous papilloma, mucoceole and pyogenic granuloma. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] To the authors knowledge, this is the first case reported where OFM has resembled the appearance of DG.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, they are often diagnosed as gingival hyperplasia, fibroma, pyogenic granuloma or fibrous epulis. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Histopathology of OFM shows a focal myxoid degeneration of the connective tissue, possibly due to the over production of hyaluronic acid by fibroblasts during collagen production, and is the definitive diagnosis for OFM. 2 In the current case report, OFM occurred after a routine crown lengthening procedure with clinical presentation resembling that of Desquamative Gingivitis (DG).…”
Section: -17mentioning
confidence: 99%
See 1 more Smart Citation
“…There are some case reports which described simple type COF 4, 6, 10, [15][16][17][18][19][20][21]32) . On the other hand, all of the POF reports that described the histopathological diagnosis were of the WHO type 3, 12,13,23,26,27,30,[33][34][35][36][37][38] , and this is the first report referring to a simple type POF in the English literature. The histopathological findings of OF showed the proliferation of elliptical and spindle-shaped cells, and fibrous connective tissue containing a small amount of odontogenic ectodermal mesenchymal tissue like a mucoid matrix (Fig.…”
Section: Figure 5 the Histopathological Findings (H-e Staining)mentioning
confidence: 99%
“…In this respect, it was considered to be a simple type POF [25][26][27][28][29][30][31] . There are some case reports which described simple type COF 4, 6, 10, [15][16][17][18][19][20][21]32) .…”
Section: Figure 5 the Histopathological Findings (H-e Staining)mentioning
confidence: 99%